P033 Periostin regulates ER-stress mediated intestinal subepithelial myoﬁbroblasts function to promote ﬁbrosis in Crohn's disease. (25th January 2019) - Li, C; Kuemmerle, J
Abstract: Background: Periostin is a secreted matricellular protein and a major component of the extracellular matrix (ECM) that contributes to intestinal fibrosis in the patients with fibrostenotic Crohn's disease. Currently, intestinal fibrosis has no efficient treatment. Previous studies showed that endoplasmic reticulum (ER) stress in intestinal epithelial cells plays a role in the pathogenesis of Crohn's disease. ER stress is also involved in the development of other fibrotic diseases. Subepithelial myofibroblasts (SEMF) are key drivers of intestinal fibrosis. However, the role of periostin in SEMF during the ER stress-mediated intestinal fibrosis in Crohn's disease remains unknown. Methods: SEMF will be isolated from the patients with each Crohn's disease phenotype and placed into 3D organoid culture. Periostin expression in freshly isolated and cultured cells was determined by western blot and qRT-PCR. Its interaction with integrin αvβ3 was confirmed by proximity ligation hybridisation assay. Knockdown of periostin in cells was accomplished with siRNA. TGF-β1 was measured by ELISA. Proliferation was measured by WST-1 assay. Migration by wounding assay. Results: Periostin expression increased 9.3 ± 0.4 fold in vimentin staining-positive SEMF isolated from affected ileum of fibrostenotic Crohn's disease (Montreal B2) compared with normal ileum in the same patient. Periostin protein was not detected in patients with other phenotypes (Montreal B1 or B3). In the presence of 10 ng/ml IL-6 significantly increased periostin protein expression and its interaction with integrin αvβ3 in SEMF compared with controls. ER stress induced by tunicamycin elicited cell proliferation and enhanced migration was inhibited by 51 ± 3.1% and 53 ± 2.6% when periostin was knocked down in SEMF compared with scrambled controls. In addition, αvβ3-dependent activation of latent TGF-β1 was inhibited by 40 ± 2.1% and 25 ± 2.3% with knockdown of periostin in both control cells and cells with subjected to ER Stress. Conclusions: Periostin promotes SEMF proliferation and migration. Periostin interacts with integrin αvβ3 and regulates latent TGF-β activation during ER stress-induced fibrosis.